Pengaruh Harga dan Kualitas Layanan terhadap Kepuasan Pelanggan Jasa Transportasi Online Grab - Gebril Ketrina Tarigan; Agus Edi Rangkuti; Martolop Sinambela; Safaruddin Safaruddin; Enda Surbakti (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
Medan City, as one of the centers of economic and population growth which is experiencing significant disruption in population and urban activities, along with the increasing population in Medan City, one of the problems often faced by users of transportation facilities is traffic jams. Motorbike taxis are the community's choice of solution to minimize traffic jams and save time. One of them is the online motorcycle taxi provider company, namely Grab. The large number of companies offering a variety of similar products at lower prices creates tough competition to increase sales. Therefore, improving product quality is something that must be done in order to increase customer satisfaction. This research aims to determine and analyze the influence of price and service quality on customer satisfaction with Grab's online transportation services. This research method is quantitative with a descriptive research type which includes validity testing, reliability testing, classical assumption testing, hypothesis testing (t test, f test, and coefficient of determination R2). The data analysis technique used in this research is multiple linear regression analysis using SPSS version 25 with a total of 100 respondents obtained from the lameshow formula. The data collection technique in this research is distributing questionnaires and literature study. Based on the research results, price (X1) and service quality (X2) simultaneously have a positive and significant effect on customer satisfaction (Y). The research results show that the price variable has an influence on the Grab customer satisfaction variable in the city of Medan with a tcount value of 5.303 > ttable 1.985 and the Service Quality variable also influences Grab customer satisfaction with a tcount value of 4.520 > ttable 1.985 with a significance level of 0.000 < 0.05. The price and service quality variables influence the Grab customer satisfaction variable in the city of Medan simultaneously with an F Calculated Test value of 85.337 with a significance level of 0.000. The results of the research coefficient of determination (R2) show that price and service quality are able to explain an influence of 63.0%. on customer satisfaction variables. Meanwhile, the remaining 37.0% is influenced by variables not examined in this research.